Pengaruh Pengalaman Wisatawan Dan Citra Destinasi Terhadap Keputusan Berkunjung - Sariyowan, Noudricha Michelle; Imam Ardiansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of tourist experience and destination image on the decision to visit Rawa Belong Silat Village, known as an urban cultural tourism destination in West Jakarta. The study uses a quantitative approach with independent variables of tourist experience (X1) and destination image (X2), and the dependent variable of visiting decision (Y). Data were collected through questionnaires distributed to 96 tourists who had visited the village, then analyzed using multiple linear regression with validity, reliability, and classical assumption tests using SPSS. The results showed that tourist experience significantly influenced the decision to visit (β = 0.441; sig. 0.000), with the emotional (involvement in culture) and intellectual (acquisition of new knowledge) dimensions as the dominant predictors. Destination image also had a significant influence (β = 0.365; sig. 0.000), mainly supported by the uniqueness of Betawi silat culture and cognitive image related to facilities. Simultaneously, both variables contributed 49.8% (R² = 0.498) to the decision to visit. The research conclusion confirms that tourist experience, particularly the emotional and intellectual aspects, as well as the image of cultural uniqueness, are key factors determining visit interest. The practical implications of these findings are the need for managers to: (1) develop interactive activities such as silat workshops and participatory cultural performances to strengthen the emotional-intellectual experience; (2) utilize digital marketing strategies that highlight the authentic identity of Betawi silat; and (3) improve the quality of supporting facilities to strengthen the cognitive image of the destination. Keywords: Betawi Culture, Cultural Tourism, Destination Image, Tourist Experience, Tourism Village, Visit Decision.